Greater superficial petrosal nerve and its surgical importance: a review - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2021)
The greater superficial petrosal nerve (GSPN) is an important but often underappreciated branch of the facial nerve. The GSPN is a mixed nerve which contains both sensory and parasympathetic fibers. It serves as the motor root of the pterygopalatine (sphenopalatine) ganglion. GSPN has a long course which passes across the middle skull base between the petrous bone and dura mater and running through the foramen lacerum. It then incorporates to the deep petrosal nerve and crosses along the pterygoid canal to the pterygopalatine ganglion. The postganglionic nerve fibers innervates the lacrimal glands, nasal mucosa and palatal mucosal glands via branches of the zygomatic nerve/zygomaticotemporal branch, sphenopalatine, greater palatine, lesser palatine nerves and pharyngeal nerve. Surgical anatomy of the GSPN nerve is often unfamiliar to many clinicians. As this nerve is usually unrecognized without use of high resolution microscope or endoscope, its anatomical knowledge is essential for surgeons basically otologists and other head and neck surgeon to minimize the risk of injury during surgical intervention. This review article surely increases the precise knowledge of the GSPN including its embryology, surgical anatomy, blood supply, relations with other structures and imaging.